ACTIVATION VOLUMES FOR OXYGEN EXCHANGE BETWEEN THE GAO4AL12(OH)24(H2O) 127+(AQ) (GAAL12) POLYOXOCATION AND AQUEOUS SOLUTION FROM VARIABLE PRESSURE 17O NMR SPECTROSCOPY - Loring J.; Yu P.; Phillips B.L.; Casey W.H. (My University, 2004)
Activation volumes for exchange of oxygen between bulk aqueous solution and sites in the GaO4Al12(OH)24(H2O)127+(aq) (GaAl12) complex were measured by variable-pressure 17O NMR techniques. Near 322 K, rates of exchange for the less labile set of bridging hydroxyls in the GaAl12 decrease by a factor of about two with increasing pressure from 0.1 to 350 MPa. These data indicate a substantially positive activation volume of ΔV‡ = +7 ± 1 cm3/mol, which is the first activation volume measured for a bridging hydroxyl in a polynuclear complex. This result suggests significant bond-lengthening in the activation step. Electrostriction effects should be small because exchange occurs via a pH-independent path under the experimental conditions. The second, more labile set of bridging hydroxyls exchange too rapidly for the variable-pressure techniques employed here. The exchange of bound-water molecules on the GaAl12 was observed at P = 350 MPa using the 17O-NMR line-broadening technique. Comparison with previous measurements at 0.1 MPa indicates decreasing line width from 0.1 to 350 MPa for temperatures at which exchange dominates, yielding an activation volume of ΔV‡ = +3(± 1) cm3/mol. This activation volume is smaller than the value for the Al(H2O)63+ complex, suggesting that water exchange on the larger GaAl12 complex has less dissociative character although the average charge density is lower.